Prevalence of Transitional Vertebra in Lumbar Disc Herniation in Bangabandhu Sheikh Mujib Medical University (Bangladesh Journal of Neurosurgery, 2024)
Background: Lumbosacral transitional vertebrae (LSTV) occur as a congenital anomaly in the segmentation of lumbosacral spine that occur during intrauterine life. LSTV includes lumbarization and sacralization of the lumbosacral region. A transitional vertebra(TV) may have varying formations, the common feature being an atypical lumbosacral articulation between transverse process of the most inferior lumbar vertebra and the sacrum. There has been a lot of discussion regarding the prevalence of LSTV in lumbar disc herniation(LDH). Most of the studies showed increased prevalence while other studies showed TV is an incidental finding and there is no increased prevalence in LDH. LDH is a quiet common ailment encountered in neurosurgical practice. Numerous causes have been attributed to it. LSTV might have great importance in patients who clinically seem to have LDH where it’s presence in plain X-ray might provide a supportive evidence for diagnosis and it can help to counsel the patient. We will be able to recommend a plain x-ray of lumbosacral spine first, having history and clinical findings suggestive of LDH and can save the cost of MRI investigation until decision for operation. Beside this LSTV is an important entity for spinal surgeons , radiologists and also for those who do interventional procedures in the spine. For this reason the prevalence of TV in LDH should be known. This study was not carried out in our country yet. So this study will enrich our demographic information and will also help the spinal surgeons to counsel the patients about their congenital spinal morphological variation and different facts related with this. Objectives: General objective of this study is to observe the prevalence of LSTV in patients with LDH. Specific objective of this study was to identify the diathroidal joint or fusion between transverse process of last lumbar vertebra and ala of sacrum, to count the vertebral number from C2 to S1 in whole spine screening film, to identify the transitional vertebra as sacralization or lumbarization or absence of TV, to predict the future possibility of development of LDH from plain X-ray of lumbosacral spine. Methods: This study was a cross sectional type of observational study and was conducted in Department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University (BSMMU). The patients (N=45) who fulfilled the selection criteria was enrolled in this study. Patient’s data were recorded in a predetermined data sheet. Patients were informed in details about the study, its merits and demerits in easy and understandable language and then informed consent was taken. Also assurance was given that all the information and records would be kept confidential and the study result would help the neurosurgeons to counsel the patients with LSTV about future possibility of development of LDH from plain X-ray of lumbosacral spine. This study was not responsible for any additional harm to the patient and study had no potential risk to the patient and no experimental drugs were used in this study. Results: A total of 45 patients of LDH were studied to see the prevalence of lumbosacral TV in LDH. Based on history and clinical findings, 100% of patients presented with low back pain, 100% of patients presented with sciatica, and 62.2% presented with gait difficulty and 02.2% of patients presented with cauda equina syndrome. Mean age of patients having LDH herniation was 38.08 ± 10.15 years. LSTV was found in 31.11% of patients with LDH. In this study, LSTV was diagnosed by plain X ray of Lumbosacral spine (A/P view) and supplemented with MRI of L/S spine with screening of whole spine (in most cases). Diagnosis of transitional vertebra was done by researcher and was further confirmed by guide and faculty members of BSMMU. In relation to gender, prevalence of LSTV in male was 25.9% and in female was 38.9% which indicated higher prevalence of TV in female but this is not statistically significant (p value 0.356).Incidence of disc herniation in patients with TV was at the space above the transition in 85.7% of cases. The most likely explanation for this is that the motion segment cephalad to the LSTV has to bear additional stresses by virtue of it being juxtaposed to a relatively non-mobile segment Conclusion: This study reveals that the prevalence of LSTV in LDH is 31.11% which is near the upper limit of its prevalence(according to literature). Association of TV with LDH can not be obtained as a control group of patient without LDH was not considered. So further study should be carried out incorporating large number of patients with control group with long study period to generalize the findings to target population.Bang. J Neurosurgery 2023; 12(2): 76-85